Evaluation of Antimalarial Activity and Toxicity of a New Primaquine Prodrug - Davanco, Marcelo Gomes [UNESP]; Campos Aguiar, Anna Caroline; Santos, Leandro Alves dos [UNESP]; Padilha, Elias Carvalho [UNESP]; Campos, Michel Leandro [UNESP]; Andrade, Cleverton Roberto de [UNESP]; Fonseca, Luiz Marcos da [UNESP]; Santos, Jean Leandro dos [UNESP]; Chin, Chung Man [UNESP]; Krettli, Antoniana Ursine; Peccinini, Rosangela Goncalves [UNESP] (Public Library Science, 2014)
Plasmodium vivax is the most prevalent of the five species causing malaria in humans. The current available treatment for P. vivax malaria is limited and unsatisfactory due to at least two drawbacks: the undesirable side effects of primaquine (PQ) and drug resistance to chloroquine. Phenylalanine-alanine-PQ (Phe-Ala-PQ) is a PQ prodrug with a more favorable pharmacokinetic profile compared to PQ. The toxicity of this prodrug was evaluated in in vitro assays using a human hepatoma cell line (HepG2), a monkey kidney cell line (BGM), and human red blood cells deficient in the enzyme glucose-6-phosphate-dehydrogenase (G6PD). In addition, in vivo toxicity assays were performed with rats that received multiple doses of Phe-Ala-PQ to evaluate biochemical, hematological, and histopathological parameters. The activity was assessed by the inhibition of the sporogonic cycle using a chicken malaria parasite. Phe-Ala-PQ blocked malaria transmission in Aedes mosquitoes. When compared with PQ, it was less cytotoxic to BGM and HepG2 cells and caused less hemolysis of G6PD-deficient red blood cells at similar concentrations. The prodrug caused less alteration in the biochemical parameters than did PQ. Histopathological analysis of the liver and kidney did show differences between the control and Phe-Ala-PQ-treated groups, but they were not statistically significant. Taken together, the results highlight the prodrug as a novel lead compound candidate for the treatment of P. vivax malaria and as a blocker of malaria transmission.